Bekatul Beras Hitam Terfermentasi Memperbaiki Kondisi Kolon Mencit yang Diinduksi Senyawa Karsinogen Azoxymethane - Nouverra Nadya Putri; Slamet Budijanto; Endang Prangdimurti; Bambang Pontjo (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2023)
Worldwide, colon cancer has become the fourth cause of death in terms of cancer. A high fiber and antioxidants diet help promote a healthy diet and prevent colon cancer. Black rice bran has high content both in fiber and phenolic. The aim of this research was to observe the potential of fermented black rice bran in improving colon conditions profiles of azoxymethane (AOM)-induced mice, comprising lactic acid bacteria (LAB) colony count, short-chain fatty acids (SCFAs) concentration, and malondialdehyde (MDA). Rhizopus oligosporus was used for fermenting the black rice bran. Five weeks old male Balb/c mice were divided into four groups (n=6) based on their diets. AOM was injected intraperitoneally and Dextran Sodium Sulphate was added to their drinking water, thus initiating inflammation in the colon. The number of LAB in faeces at the end of intervention in the groups of fermented rice bran group (FRB) (9.04±0.04 log CFU) and non-fermented rice bran group (NRB) (8.99±0.04 log CFU) were higher than that of the positive control group (8.33±0.06 log CFU/g) but fewer as compared to the negative control (9.63±0.05 log CFU). The concentrations of SCFAs (acetic acid, propionic acid and butyric acid) of the cecum content in the NRB group (11.92±0.00, 2.31±0.01 and 3.41±0.01 mM) were higher in the positive control group (8.90±1.30, 1.60±0.16 and 2.27±0.31 mM). As compared to the positive control group, the concentration of propionic acid of cecum content in the FRB group was higher (2.09±0.32 mM), but the concentrations of acetic acid and butyric acid were indifferent. The MDA level of the FRB group (1.41±0.03 µmol) was lower thanthat of the NRB group (1.88±0.05 µmol), and the MDA level of NRB was lower than that of the positive control group (2.03±0.09 µmol). The results showed that both FRB and NRB had a positive role in increasing the number of LAB, ALRP concentrations, and decreasing MDA levels in AOM-induced mice colons.